Role of platelet indices in pre-eclampsia: a case-control study at teaching hospital, Nepal - Choudhary, Prabesh; Pandit, Narendra; Nepal, Niraj; Yadav, M (Journal of Pathology of Nepal, 2023)
Background: Preeclampsia is one of the major health-related ailments causing increased maternal morbidity and mortality, and complicates up to 10% of pregnancies. The study aims to find out the utility of platelet indices for early prediction of preeclampsia.Materials and Methods: It was a prospective case-control study that included a total of 84 patients (42 in the study group with preeclampsia and 42 controls with normal blood pressure) during a one-year study period. Fresh blood samples (2 ml) were collected for the platelet indices - platelet count (PC), plateletcrit (PCT), mean platelet volume (MPV), and platelet distribution width (PDW) – and were analyzed by fully automated cell counter by impedance method, and compared between the two groups.Results: Both groups were comparable in terms of age, parity, gestational period, and body mass index. The PC and MPV showed a significant difference; (1.98±0.7 vs. 2.42±0.8; p= 0.01) and (12.44±0.6 vs.10.0±0.48; p= 0.03) between the two groups respectively.  However, the difference between the two groups was not statistically significant for PCT and PDW.Conclusions: The low platelet count and an increased mean platelet volume were significant in patients with preeclampsia compared to the control group. It could be a marker for early diagnosis of preeclampsia in pregnancy.